2022
DOI: 10.3390/molecules27061894
|View full text |Cite
|
Sign up to set email alerts
|

A Helquat-like Compound as a Potent Inhibitor of Flaviviral and Coronaviral Polymerases

Abstract: Positive-sense single-stranded RNA (+RNA) viruses have proven to be important pathogens that are able to threaten and deeply damage modern societies, as illustrated by the ongoing COVID-19 pandemic. Therefore, compounds active against most or many +RNA viruses are urgently needed. Here, we present PR673, a helquat-like compound that is able to inhibit the replication of SARS-CoV-2 and tick-borne encephalitis virus in cell culture. Using in vitro polymerase assays, we demonstrate that PR673 inhibits RNA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…A pyridobenzothiazole compound, HeE1-2Tyr, initially characterized as an inhibitor of flavirus RdRp interacting with its RNA-binding sites [ 36 ], was shown to inhibit SARS-CoV-2 RdRp with IC 50 of 27 μM [ 37 ]. Furthermore, a helquat-like compound PR673 was shown to inhibit SARS-CoV-2 RdRp with IC 50 of ~4 μM [ 38 ]. However, the effects of both compounds on RNA binding by SARS-CoV-2 RdRp were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…A pyridobenzothiazole compound, HeE1-2Tyr, initially characterized as an inhibitor of flavirus RdRp interacting with its RNA-binding sites [ 36 ], was shown to inhibit SARS-CoV-2 RdRp with IC 50 of 27 μM [ 37 ]. Furthermore, a helquat-like compound PR673 was shown to inhibit SARS-CoV-2 RdRp with IC 50 of ~4 μM [ 38 ]. However, the effects of both compounds on RNA binding by SARS-CoV-2 RdRp were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Takové umělé inteligence by byly přínosné zejména tam, kde je generování experimentálních krystalových struktur velmi náročné. Například zatímco identifikace inhibitorů virových polymeras, ať už jakoukoli metodou, je poměrně přímočará [78][79][80][81] , získání jejich krystalové struktury může být velmi náročné, protože je třeba připravit krystaly ternárního komplexu, který obsahuje také RNA a její sekvence musí být optimalizována. V takových situacích jsme se dříve často spoléhali na modely odvozené z počítačových simulací 82 .…”
Section: Budoucí Vývojunclassified
“…1C) which is structurally related to the title compound HeliDye1. 23 Helquat dye PR673 inhibited RNAdependent RNA polymerase (key enzyme for the replication of RNA viruses) of all seven tested viruses (including Zika, yellow fever and SARS-CoV-2 viruses). Later, in a study searching for anti-HIV-1 Inhibitors, we observed interaction of several helquat dyes with G-quadruplexes (manuscript in preparation).…”
Section: (D)mentioning
confidence: 99%